2012
DOI: 10.1001/archinternmed.2012.770
|View full text |Cite|
|
Sign up to set email alerts
|

Effectiveness and Safety of Procalcitonin-Guided Antibiotic Therapy in Lower Respiratory Tract Infections in “Real Life”

Abstract: isrctn.org Identifier: ISRCTN40854211.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(49 citation statements)
references
References 39 publications
(21 reference statements)
6
42
0
Order By: Relevance
“…In a computer-based model, retrospective data analysis from 1,312 ICU patients and an arbitrary use of PCT-algorithm showed substantial reduction in the treatment costs, based on the German DRG system (DRG, diagnosis related groups, a system of disease related reimbursement) [56]. Two minor studies in France did not see a beneficial effect of PCT based algorithm, but others confirmed the significant reduction of antibiotic use in the clinical routine as well [57, 58]. Further studies are under way, e.g.…”
Section: Possible Side Effectsmentioning
confidence: 99%
“…In a computer-based model, retrospective data analysis from 1,312 ICU patients and an arbitrary use of PCT-algorithm showed substantial reduction in the treatment costs, based on the German DRG system (DRG, diagnosis related groups, a system of disease related reimbursement) [56]. Two minor studies in France did not see a beneficial effect of PCT based algorithm, but others confirmed the significant reduction of antibiotic use in the clinical routine as well [57, 58]. Further studies are under way, e.g.…”
Section: Possible Side Effectsmentioning
confidence: 99%
“…In a prospective, observational, international, multicenter, quality control survey (ProREAL) (1759 patients) of PCT-guided antibiotic therapy for lower respiratory tract infection, the duration of antibiotic therapy was significantly shortened if the algorithm of PCT was followed. The mean overall reduction was approximately 20 % (from 7.4 to 5.9 days) [4].Other previous randomized controlled trials have suggested that using clinical algorithms based on PCT results in reduced antibiotic use without a deleterious effect on clinical outcomes. These results have been supported by strong evidence in respiratory infections, and the studies reported approximately 20-50 % reduction in antibiotic usage in patients with lower respiratory tract infection [4-6, 54, 55].…”
Section: Pct-guided Antibiotics Strategymentioning
confidence: 75%
“…Procalcitonin (PCT) is widely used to differentiate bacterial infections from non-bacterial infections or other inflammatory conditions, and growing evidences has suggested that PCT reliably differentiates sepsis from SIRS. Moreover, it has been recently shown that PCT is a valuable tool to guide antibiotic treatment in patients with bacterial infections [2][3][4][5][6].The aim of this review is to summarize the current evidence for PCT in different infections and clinical settings, and discuss the strengths and limitations of PCT.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, robust clinical data on this topic are still scarce. Two publications in respiratory tract infections in the outpatient setting could show a sigificant reduction of antibiotic use if a PCT-guided algorithm was employed [37,38]. In septic intensive care patients, a retrospective study demonstrated that implementation of a PCT-based algorithm was associated with a significantly shortened length of antibiotic treatment over a 5-year observation period [10].…”
Section: Discussionmentioning
confidence: 99%